Application of Strategic Management Principles as an Adaptive Strategy for Coal-Fired Power Plants (PLTU) in the Era of Decarbonization - Dr. Rio Afrianda (Prodi Magister Manajemen Universitas Dirgantara Marsekal Suryadarma, 2026)
The global energy transition and decarbonization agenda have positioned coal-fired power plants (PLTU) in a strategic dilemma, as they remain essential for maintaining electricity supply reliability while simultaneously facing increasing pressure to reduce carbon emissions. This condition requires PLTU organizations to develop adaptive strategies that can respond effectively to regulatory changes, stakeholder demands, and environmental uncertainty. This study aims to analyze the role of strategic management principles as an adaptive strategy for PLTU in the era of decarbonization and to examine their implications for the sustainability of organizational performance, with decarbonization pressure acting as a moderating variable. The study employs a quantitative, causal-explanatory research design, with data collected through structured questionnaires from managerial and supervisory personnel working in PLTU in Indonesia. Data analysis is conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate that the application of strategic management principles has a positive and significant effect on adaptive strategy, indicating that systematic processes such as environmental scanning, strategic formulation, implementation, and strategic control play a critical role in enhancing organizational adaptability. Furthermore, adaptive strategy is found to have a significant positive impact on the sustainability of PLTU performance, enabling organizations to maintain operational stability and efficiency under increasing environmental and regulatory pressures. The moderating analysis reveals that decarbonization pressure strengthens the relationship between strategic management principles and adaptive strategy, suggesting that external environmental pressure can function as a catalyst for strategic transformation when supported by strong strategic capabilities. This study concludes that the sustainability of PLTU performance in the era of decarbonization is highly dependent on the effective integration of strategic management principles into adaptive strategies, thereby positioning strategic management as a key enabler of organizational resilience during the energy transition.